Arbuscular Mycorrhizal Fungi Encourage Drought Tolerance Of Chlorophytum Borivilianum By Enhancing Antioxidant Enzyme System (Applied Biological Research, 2012)
Chlorophytum borivilianum, due to the presence of high valued  industrially important steroidal saponins in its roots, has attracted  pharmacological societies worldwide and motivated the farmers of arid  and semi-arid zones to cultivate this medicinal herb on commercial scale.  However, drought stress is a major abiotic constraint in the successful  cultivation of this crop in these areas. One possible way to enhance its  production is to improve its drought tolerance through arbuscular  mycorrhizal symbiosis. The mechanism by which mycorrhizal symbiosis  protects the plants against reactive oxygen species, induced by drought  stress, is investigated by evaluating the activity of a set of antioxidant  enzymes in relation to different mycorrhizal inocula at various growth  stages. The influence of three mycorrhizal inocula viz., Glomus  fasciculatum, G. intraradices and G. mosseae on superoxide dismutase,  catalase, glutathione reductase, glutathione-s-transferase, polyphenol  oxidase and peroxidase enzyme activities were evaluated in well-watered  and drought stressed conditions. The result revealed that the entire mycorrhizal plant materials showed higher drought tolerance effect than  non-mycorrhizal ones by enhancing antioxidant enzyme activities.  Antioxidant activities were more at 180 days of crop harvest. Therefore,  it is recommended to harvest C. borivilianum roots at 180 days crop age.  Mycorrhizal drought-stressed roots showed significantly higher anti oxidant activities than the well-watered conditions. Thus, it can be  assumed that higher antioxidant activities in roots of mycorrhizal plants  might have contributed to alleviate the oxidative damage to biomolecules.  The cultivation of C. borivilianum with arbuscular mycorrhizae in arid zone, therefore, can be a value addition against drought stress.
Keywords: Antioxidant enzymes; arbuscular mycorrhiza; Chlorophytum borivilianum; drought stress; Glomus species